Quo Vadis ASEAN Security Amidst the United States-China Rivalry in the Southeast Asia Region - Marie, Nurul Titi; Handayani, Prawita Meidy; Wibawati, Samti Wira (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
Tensions between the United States and China intensify globally, particularly in Southeast Asia. Therefore, ASEAN countries should re-assess the ties between these two great powers, both within the ASEAN region and with external counterparts. Given the strategic value of the region, Southeast Asia has become the venue for strategic competition between the United States and China over the past decade. Therefore, rowing the ASEAN’s boat among the two gigantic reefs in the ocean requires ASEAN resilience as a Community to overcome the current and future challenges. Potential conflicts intra-ASEAN could be entry points for major powers to weaken ASEAN’s unity. The study aims to analyze the most suitable approach for ASEAN regionally to deal with the challenges and to meet the expectations for a sustainable ASEAN Community and assess whether ASEAN’s orientation in maintaining neutrality against major powers remains suitable to serve the strategic interests of the member states in the current environment. In this regard, a qualitative method and concepts of Amalgamated Security Community and Pluralistic Security Community are applied to analyze the study. The results of the study show realistic calculation can never be overlooked to preserve sustainable common strategic interests for the member states, which include economic growth on the one hand, and stable regional peace on the other hand. In this regard, “a manageable United States-China rivalry” by a solid ASEAN Pluralistic Security Community in the region guarantees more sustainability of national strategic interests for its member states and ASEAN.